Narratives of de-secularization in international relations. Issue 1 (2nd January 2017) - Hurd, Elizabeth Shakman
ABSTRACT: This article explores how a particular narrative of de-secularisation, the 'restorative narrative, ' is shaping US foreign religious policy and practice. It develops two arguments about efforts to stabilize religion as an object of governance and restore it to international politics and public life. First, this narrative re-instantiates and energizes particular secular-religious and religious-religious divides in ways that echo the narratives of secularisation that it claims to challenge and transcend. Second, it contributes to the emergence of new forms of both politics and religion that are not only subservient to the interests of those in power but marginalize a range of dissenting and nonconforming ways of life. This has far-ranging implications for the politics of social difference and efforts to realize deep and multidimensional forms of democratization and pluralization. The argument is illustrated through discussions of recent developments at the US State Department, the evolving practices of US military chaplains, and the politics of foreign religious engagement in the context of the rise of Turkish Islamist conscientious objectors.